2006
DOI: 10.1210/jc.2006-0076
|View full text |Cite
|
Sign up to set email alerts
|

Premature Mortality in Patients with Addison’s Disease: A Population-Based Study

Abstract: Compared with the background population, we observed that the risk ratio for death was more than 2-fold higher in patients with Addison's disease. Cardiovascular, malignant, and infectious diseases were responsible for the higher mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
368
6
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(403 citation statements)
references
References 26 publications
11
368
6
18
Order By: Relevance
“…Afterwards, it has become increasingly clear that, on the contrary, despite glucocorticoid replacement therapy, mortality rate and morbidity remain increased in patients with adrenal insufficiency as compared to the general population [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, it has become increasingly clear that, on the contrary, despite glucocorticoid replacement therapy, mortality rate and morbidity remain increased in patients with adrenal insufficiency as compared to the general population [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is a more than a two-fold increase in relative risk of death in Swedish patients with AD, predominantly due to cardiovascular, malignant, and infectious diseases [7,8]. The same for Norwegian patients with AD, particularly males, presenting with an increased risk of premature death due to infections, sudden death and acute adrenal failure [9].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies in patients with both secondary 8,9 and primary adrenal insufficiency 10,11 used data registries and showed that they were at increased mortality risk, with some suggesting that endocrine and infectious causes contributed to this. 10,11 Subsequently, in a Swedish study 12 of patients with hypopituitarism, all 15 cases of death from infections occurred in patients with hypocortisolism.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…10,11 Subsequently, in a Swedish study 12 of patients with hypopituitarism, all 15 cases of death from infections occurred in patients with hypocortisolism. Eight of these patients had a documented adrenal crisis, and 7 of these 8 died at home or upon arrival to the hospital.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Recently, it has been demonstrated that the patients with PAI and SAI show a significantly reduced subjective health status (SHS), irrespective of age, sex, concomitant disease, and primary or secondary origin of AI (3,4). Importantly, also increased mortality has been described (5,6). These observations have renewed the discussion of optimal replacement treatment in AI after about 50 years of almost unchanged regimens.…”
Section: Introductionmentioning
confidence: 99%